2012
DOI: 10.1038/npp.2012.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of IQ-Modulated Association Between ZNF804A Gene Polymorphism and Cognitive Function in Schizophrenia Patients

Abstract: ZNF804A gene polymorphism rs1344706 has been suggested as the most compelling case of a candidate gene for schizophrenia by a genome-wide association study and several replication studies. The current study of 570 schizophrenia patients and 448 controls again found significantly different genotype frequencies of rs1344706 between patients and controls. More important, we found that this association was modulated by IQ, with a stronger association among individuals with relatively high IQ, which replicated resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
3
27
2
2
Order By: Relevance
“…Interestingly, studies investigating the polymorphism in the ZNF804A gene (rs1344706), known to upregulate genes implicated in the TGF-β signaling,10 have shown its correlation with several domains of cognitive performance including episodic and working memory, executive functions, verbal learning, and recall 5761. Most interestingly, the ZNF804A gene polymorphism (rs1344706) has been found to predict poorer executive control of attention in schizophrenia, overlapping partially with the results of our study 60.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, studies investigating the polymorphism in the ZNF804A gene (rs1344706), known to upregulate genes implicated in the TGF-β signaling,10 have shown its correlation with several domains of cognitive performance including episodic and working memory, executive functions, verbal learning, and recall 5761. Most interestingly, the ZNF804A gene polymorphism (rs1344706) has been found to predict poorer executive control of attention in schizophrenia, overlapping partially with the results of our study 60.…”
Section: Discussionsupporting
confidence: 85%
“…Further studies have linked ZNF804A to neurocognitive measures including verbal working memory and episodic working memory (e.g., Walters et al, 2010). However, within schizophrenia cases, the schizophrenia-associated risk allele has shown relatively preserved cognition (Walters et al, 2010; Becker et al, 2012; Van Den Bossche et al, 2012; Chen et al, 2012), whereas in healthy controls the same schizophrenia-associated risk allele appears to impart poorer performance (Lencz et al, 2010; Esslinger et al, 2011; Voineskos et al, 2011; Balog et al, 2011). The SNP in our study, rs1366842, is approximately 10kb from rs1344706 and is in modest linkage disequilibrium with this SNP (HapMap, CEU and TSI populations, r 2 = 0.40).…”
Section: Discussionmentioning
confidence: 99%
“…Following our literature search strategy, a total of 11 studies involving 15 independent samples which encompass 11573 cases and 15321 controls, as well as 101 schizophrenia trios, were identified for schizophrenia912131415161718222324, and 2 studies (including the present study) consisting of 1274 patients of BD and 1343 healthy controls was identified for BD21. Detailed information concerning the sample size and association results for each study was listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up studies conducted in different European populations have replicated this finding, suggestive that rs1344706 is probably an authentic risk SNP for schizophrenia and BD in Europeans1011. In Chinese populations, several groups have reported the association between rs1344706 and schizophrenia, subjects from which were all from northern China (Shanxi, Xinxiang and Shandong)121314. However, more studies with subjects recruited from central and Southern China ( i.e ., Jiangsu, Yunnan, Sichuan and Guangxi province) failed to replicate this association15161718.…”
mentioning
confidence: 89%